Can Laparoscopic Cholecystectomy be a Feasible Standard in a Rural set up too? - An Experience of 348 cases from a Peripheral set up of Western Nepal - Shrestha, A.L.; Shrestha, P.; Brown, D. (Kathmandu University Medical Journal, 2017)
Background Gall stone disease is a common reason for admissions in both acute and elective situations and bears significant morbidity in the rural population of western Nepal. The earlier conventional open method of treatment for the same seems to have been largely seeded by the laparoscopic approach owing to its numerous benefits. Objective To study the clinical profile of patients with symptomatic gall stones with respect to demography and to assess the feasibility of using Laparoscopic cholecystectomy as the next standard in this set up too as guided by the outcome in terms of complications, conversion rates and potential impact it bears on the health and socioeconomic status in this group. Method A retrospective analysis of all the patients undergoing an attempted laparoscopic cholecystectomy from 1st Jestha 2068 to 30th Jestha 2070 was done. Relevant medical records were reviewed to study demography, various indications for operations, intra operative events including conversions and complications. Result Of 348 patients 293(84.19%) were females and 55(15.80%) were males. The mean age was 38.46 years (range 15-76 years). Most of the patients belonged to the Palpa district of Lumbini zone and many were from other surrounding areas. Gall stone disease was commonest in people of Brahmin ethnicity. The operating time was <2 hours for most and most had an uneventful recovery with a mean hospital stay of 3.8 days. The rate of conversion to open cholecystectomy was 6.9% (24 out of 348 patients). Post operative complications were noted in 5 patients (1.42%). Of these 1 sustained a major bile duct injury (0.28%) requiring immediate conversion and repair, 3 had post operative bilioma and 1 had diffuse bleeding from the gall bladder fossa all requiring re explorations. There was no mortality in this study. Conclusion Laparoscopic cholecystectomy is a safe, reliable and a promising option even in the rural peripheral set up. Due to its well known advantages and superiority over the open conventional method and considering the impact that it holds on the overall outcome, morbidity, health and socioeconomic status of the rural population, it can be recommended as an acceptable feasible standard in rural peripheral set up.